Sosialisasi Reference Manager Mendeley Bagi Dosen-Dosen Fakultas Ekonomi, Hukum Dan Humaniora Universitas Ngudi Waluyo - Saptanto, Deswandito Dwi; Nurjanah, Ratih Laily; Pratama, Mochamad Rizqi Adhi (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
The role of lecturers in carrying out the learning and publication process certainly requires competencies that always up to date. This Community Service Program in the form of short training and mentoring aims to provide socialization about the use of the reference manager application (Mendeley) to support the improvement of lecturer competencies in the scope of education, research and community service activities as the main task of a lecturer in the Tridharma of Higher Education. Reference manager (Mendeley) is needed to facilitate the work of lecturers as well as researchers. Community service activities by providing socialization on how to use this reference manager were initiated because there are still many lecturers who still quote references from books and articles manually. This activity will be carried out using direct training methods for all lecturers at the level of the Faculty of Economics, Law and Humanities, Universitas Ngudi Waluyo. Community service activities by providing direct training using a reference manager are very useful to support the duties and obligations of lecturers in making teaching materials and materials, making scientific articles.